ANALYSIS OF ENGLISH DESCRIPTIVE TEXTS IN A BATIK MUSEUM IN INDONESIA: LANGUAGE ACCURACY AND CULTURAL REPRESENTATION - Salsabilah Suhada; Silih Warni (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to analyze the linguistic accuracy and cultural representation in English descriptive texts in a Batik museum in Indonesia. Employing a qualitative method, data were collected through documentation, and interviews with museum staff. The findings reveal recurring grammatical issues, such as article omission, word misordering, and awkward phrasing, which affect clarity and professionalism. Culturally, many texts lack depth, providing only names and origins of batik without explaining symbolic or historical context. Some translations are overly literal and fail to capture natural English expression, limiting international visitors’ understanding. The study highlights the need for improved linguistic quality and cultural depth in museum texts. It recommends strategies like transcreation and collaboration with language experts to produce informative, accurate, and culturally sensitive content for a global audience.